Upaya Guru Dalam Pembelajaran Baca Tulis Al-Qur’an untuk Meningkatkan Prestasi Belajar PAI pada Siswa Kelas VIII Fullday Di SMP Al Falah Dago - Ahmad Rifqy Ash-Shiddiqy; Nida Aya Sophia (STAI Siliwangi Bandung, 2020)
The student's ability in reading Qur'an is very important to study the Islamic religion, especially in schools. Therefore, managers need to be aware of it. This study aims to determine the efforts of teachers in learning read and write Al-Qur’an to improve learning achievement of islamic education in the students of class VIII in SMP Al Falah Dago Full day school. The approach used in this research is combination approach (mix methods) with concurent triangulation design. With a population of 62 respondents. Data collection techniques used in the form of interviews, observation, and study documentation. In analyzing the data used program IBM SPSS 21.0. Based on the qualitative results that the efforts of read and write Al-Qur’an teachers have connection with read and write Al-Qur’an's learning achievement. Hypothesis testing of this research using simple linear regression. The results of hypothesis testing show that: Achievement learn read and write Al-Qur’an class VIII Full day in category